The Meaning of The Miare Tradition: From Condolences to The Symbolisation of The Corps in The Grave - Mualimin, Mualimin; Rofi'i, Rofi'i (NALAR, 2023)
This article aims to analyse the meaning of Miare tradition for the community in Makrampai village, Sambas Regency. This study is a qualitative research with a phenomenological approach. Data were obtained by conducting in-depth interviews and participant observation. Data collection was conducted in Makrampai Village from April to September 2021. The data were then analysed using an interactive qualitative analysis model: data reduction, data display, and conclusion. This study found two essential meanings of the miare tradition for the Makrampai village community. First, the miare tradition manifests condolences and social solidarity towards members of the society who have suffered calamities, especially death. Second, the Miare tradition is a reminder and advice that every human being will definitely face death in the cycle of life.